STUDI LITERATUR: KARAKTERISTIK SENSORI KUKIS OATMEAL SEBAGAI CAMILAN RAMAH DIET - Madina H, Styla Britania Sarah Noor; Faujania, Dyva Mustika (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2024)
The addition of fiber in cookie formulations has been widely studied to create functional cookie products. Oats can be used as raw material to substitute kukis to produce low-calorie kukis which can be used as a diet-friendly snack. The aim of preparing this literature study is to determine the quality of oatmeal kukis as a diet-friendly snack by using 3 relevant journals as the main literature source. The modification to the oatmeal kukis was to substitute 60% oatmeal and 100% low-calorie sugar to reduce the number of calories in the kukis. The results of this study show that oatmeal kukis contain fewer calories than regular kukis. Apart from that, the oats which are a substitute ingredient in oatmeal kukis are a type of whole wheat which contains complex carbohydrates and dietary fiber which can provide a longer satiety effect and play a role in regulating the rate of digestion. So it can be concluded that oatmeal kukis are suitable for consumption as a snack during a diet. Keyword: cookies, diet, oatmeal, snack, characteristics, sensory